2018
DOI: 10.4174/astr.2018.95.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of gallstones after gastric resection for gastric cancer: a nationwide claims-based study

Abstract: PurposeGallstone formation is one of the most common problems after gastrectomy. This retrospective cohort study used the South Korean nationwide claims database to evaluate the incidence and risk factors of gallstone after gastrectomy for gastric cancer.MethodsAll consecutive patients who underwent gastrectomy for gastric cancer in South Korea in 2008–2010 were identified. Incidence of gallstone formation 5 years after gastrectomy in males and females, in various age groups, and after different types of gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The width of lymph node dissection has been reported as a risk factor for gallstone disease that develops after gastrectomy (3,7,12). In a study of 805 patients, Akatsu found that gallstone disease was statistically significantly higher in the D2 dissection group (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The width of lymph node dissection has been reported as a risk factor for gallstone disease that develops after gastrectomy (3,7,12). In a study of 805 patients, Akatsu found that gallstone disease was statistically significantly higher in the D2 dissection group (7).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is one of the most frequent cancers causing death worldwide; and gastrectomy constitutes the basis of surgical treatment (1). Gallstone formation after curative surgery is a common complication, and its prevalence is reported to be 15%-25% higher than the general population (2,3). It is thought that the dissection of the hepatic branch of the vagus, bypassing of the duodenum, and the changes in the release of cholecystokine cause the gallbladder stone formation after gastrectomy (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholelithiasis is known as one of the long-term complications of gastrectomy [8][9][10][11][12][13]. The incidence of gallbladder stones (GBS) after gastrectomy, as reported in many studies, ranges from 5.2 to 15.3% in Korea [9][10][11], 7.4% in China [12], and 13.6% in Japan [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several additional possible risk factors for the growth of gallbladder stones are sedentary way of life, elderly age group and family history of gallstones 9 . Gallbladder stones development is a multifactorial procedure including a large number of metabolic pathways 18 . It is claimed that females are multiple times more prone to this disease than males.…”
Section: Introductionmentioning
confidence: 99%